Perencanaan strategi bisnis rumah sakit ibu & anak - Yuniarto, Aditya; Zulkifli, Zulkifli; Derriawan, Derriawan (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this study is how to plan a business strategy for the hospital unit business, with the case study at Women & Children Hospotal (RSIA) XYZ which is private hospital type C at South Tangerang  . This research focus is to formulate a business strategy plan for the next 5 years for RSIA XYZ which is expected to be used as a reference for the company and become a benchmark for measuring the success of company performance. This research is a qualitative research with a quantitative approach with a problem approach through descriptive analysis, regarding the Business Strategy Planning at XYZ Hospital in 2020-2024. The results showed the XYZ Hospital business strategy plan by referring to the strategies from the results of the analysis that had been carried out and the right strategy was selected for RSIA XYZ which could then be compiled into work plans and programs. Not only until the next work program will also be compiled Key Performance Indicators (KPI) related to the strategic goals aimed each year.